Use of Bicycle Exercise Echocardiography for Unexplained Exertional Dyspnea - Singhal, Shalabh (Clin Cardiol, 2009)
Unexplained exertional dyspnea is a common and perplexing clinical problem. Myocardial ischemia and left ventricular systolic dysfunction are important cardiac causes, but are often not detected in these patients. Recently, exercise‐induced left ventricular diastolic dysfunction and exercised‐induced pulmonary hypertension have emerged as common alternative mechanisms. While conventional exercise treadmill echocardiography effectively diagnoses left ventricular systolic dysfunction and myocardial ischemia, it has limited ability to detect exercise‐induced diastolic dysfunction or pulmonary hypertension. The latest advances in exercise echocardiography, including utilization of tissue Doppler imaging and harmonic imaging, make noninvasive evaluation of both conventional and alternative cardiac causes of exertional dyspnea possible. These advancements, when coupled with newly designed supine exercise platforms for bicycle exercise echocardiography (BE), facilitate the detection of exercise‐induced diastolic dysfunction and pulmonary hypertension. Moreover, BE using supine ergometry additionally permits the dynamic evaluation of valvular function and interatrial shunting and detection of pulmonary arteriovenous fistula, uncommon but important causes of unexplained exertional dyspnea. Therefore, we propose that because of its superior diagnostic capabilities, BE should be included as part of a comprehensive cardiac evaluation of patients with unexplained exertional dyspnea. Copyright © 2009 Wiley Periodicals, Inc.